Directed transport of a deformable particle in confined periodic structures. (1st July 2022) - Li, Jia-Jian; Lin, Fu-Jun; Ai, Bao-Quan
Abstract: Directed transport of a deformable particle is numerically investigated in a two-dimensional periodic channel. Unlike the rigid particle, the deformable particle can pass through the channel bottleneck that is significantly smaller than the particle size. The deformable characteristics of the particle can greatly affect the directed transport of the particle. (i) For the case of active deformable particle, the self-propelled velocity can break thermodynamics equilibrium and induce the directed transport. The average velocity is a peak (or valley) function of the particle size for large (or small) self-propulsion speed. Particle softening (large shape parameter) facilitates the rectification of the particle for small particle, while it blocks the rectification for large particle. (ii) For the case of passive deformable particle, periodic oscillation of the particle size can also break thermodynamical equilibrium. There exists an optimal oscillating frequency at which the average velocity takes its maximal value. For low oscillating frequency, the average velocity is a peak function of the oscillating amplitude, while for high oscillating frequency the average velocity increases monotonically with the oscillating amplitude. Our results may contribute to the understanding of the transport behaviors of soft, deformable matter in confined structures.